Revisiting Language, Ethnicity, and Identity in the Former Yugoslavia - Greenberg, Robert (Aegean Working Papers in Ethnographic Linguistics, 2020)
This special edition on the language issues in the former Yugoslav space (AWPEL 2.1) provides some new perspectives and approaches to the study of the interplay of language, ethnicity and identity among the peoples of the former Yugoslavia. When I first began focusing on this topic in the early 1990s, the sociolinguistic and ethnographic linguistic literature on the peoples and languages of this multi-ethnic space seemed to be in its infancy. This volume reveals that the case of the former Yugoslavia has proven to be a fruitful field for scholarship in these areas of linguistic inquiry. It is pleasing to see here how younger researchers approach the complex issues arising from the breakup of Yugoslavia and the disintegration of the joint language formerly known as Serbo-Croatian or Croato-Serbian. [...]